2022
DOI: 10.1590/1678-4324-2022210592
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Sewage Sludge: Physical, Chemical, Morphological and Mineralogical Transformations

Abstract: The sewage sludge (SS) use in agriculture has been limited by the Brazilian legislation to a few situations, mainly as a precautionary measure due to inorganic pollutants and pathogens. Thus, a large amount of SS has been accumulated in landfills, with no prospect of use, generating great concern for governments and society. Thermal treatment via pyrolysis has stood out as an option for SS recycling, transforming it into a carbon-rich product known as SS biochar (SSB). Biochar from SS showed good potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Zamotaev et al (2022) presented an overview of contemporary concepts of technogenesis and soil formation in liquidated wastewater treatment plants of former sugar plants, as well as trends in changes in soil properties under the influence of the use of waste in agriculture as organic fertilisers in various natural areas. Raček et al (2022) and Fachini and de Figueiredo (2022) presented the results of the preparation and characterisation of the dried municipal sewage sludge and the so-called solid carbonaceous product, the outcome of its further processing by slow microwave pyrolysis/torrefaction. The research aims to determine the possibility of using these products for combustion in energy production, agriculture, and blue-green infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zamotaev et al (2022) presented an overview of contemporary concepts of technogenesis and soil formation in liquidated wastewater treatment plants of former sugar plants, as well as trends in changes in soil properties under the influence of the use of waste in agriculture as organic fertilisers in various natural areas. Raček et al (2022) and Fachini and de Figueiredo (2022) presented the results of the preparation and characterisation of the dried municipal sewage sludge and the so-called solid carbonaceous product, the outcome of its further processing by slow microwave pyrolysis/torrefaction. The research aims to determine the possibility of using these products for combustion in energy production, agriculture, and blue-green infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The antibiotics (sulfamethazine, tetracycline, and chloramphenicol) can be removed from the aqueous solution with original steel chips and nitrogen plasma-modified steel chips . However, through literature comparison, it was found that the metal active species in the waste slag-based adsorbent and their content had a great impact on the removal of pollutants, and the effect was not consistent. Unlike pure synthetic adsorbents, solid waste-based adsorbents contain multiple active adsorption sites that can act simultaneously in practical applications. In addition, the competitive synergy of composite pollutants also deepens the complexity of the adsorption mechanism path.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, a transformação desse resíduo em biocarvão, subproduto rico em carbono, através do processo térmico, pirólise, torna-se uma boa opção. Pois, esse processo transforma o biossólido em um material livre de organismos patogênicos e ricos em nutrientes como nitrogênio, fósforo, cálcio e zinco (PAZ-FERREIRO et al, 2018;FACHINI;FIGUEIREDO, 2022).…”
Section: Introductionunclassified